Enhanced Microwave Electric Field Measurement With Cavity-Assisted Rydberg Electromagnetically Induced Transparency - Li, Shaohua; Yuan, Jinpeng; Wang, Lirong; Xiao, Liantuan; Jia, Suotang (Frontiers in Physics, 2022)
We report a scheme for enhancing microwave electric field measurement by cavity-assisted Rydberg electromagnetically induced transparency in the 87Rb coherent atomic system. The vacuum Rabi splitting appears when the probe field is strongly coupled with intracavity atoms. The cavity-assisted electromagnetically induced transparency with dual-peak profile is observed as a strong coupling laser is further introduced into the optical ring cavity. The optimal atomic density, resulting in an appropriate vacuum Rabi splitting interval and cavity-assisted electromagnetically induced transparency amplitude, is determined for the coupling effect criterion of the probe field and intracavity atoms. Finally, the cavity-assisted electromagnetically induced transparency is employed to accurately measure the microwave electric field strength, and a measurement sensitivity factor of about 2 is improved owing to an enhanced photon–atom interaction. This study is beneficial for the development of compact, broadband, and self-calibrating microwave receivers.